Prevalence of Endometrial Cancer and Correlation between Body Mass Index and Histopathological Finding of Endometrial Tissue for Prediction of Endometrial Cancer: Retrospective Analysis of Electronic Medical Records - Petcharoen, Chatpisit; Khuakoonratt, Nathaya; Smanchat, Buppa; Bhamarapravatana, Kornkarn; Suwannarurk, Komsun (Asian Pacific Journal of Cancer Care, 2026)
Introduction: Aim of the study was to investigate the prevalence and correlation of body mass index (BMI) and histopathological finding of the endometrium for prediction of endometrial hyperplasia/ endometrial cancer (EH/EC) in women with abnormal uterine bleeding (AUB). Materials and methods: This retrospective cohort study was conducted at the outpatient clinic, department of obstetrics and gynecology, Bhumibol Adulyadej Hospital, Royal Thai Airforce, Thailand from January 2021 through December 2024. The subjects were female who presented with AUB and underwent endometrial biopsy (EB). Demographic data was collected and analyzed. Results: A total of 1,408 cases were recruited. Mean age of participants were 49.9 years old. There were 430 and 978 cases of age less (A1) and more than (A2) 45 years old. Subjects A2 group had significantly more parity (74.9% vs 59.3%), diabetes mellitus (10.2% vs 0.9%), hypertension (20.6% vs 3.5%) and dyslipidemia (13.1% vs 1.6%) than those in A1 group. Polycystic ovarian syndrome was commonly found among subjects in A1 group than A2 group (2.8% vs 0.2%, p-value < 0.001). Prevalence of EC was 3.5 (54/1, 540) percent. Percentage of EH/EC was 14.2 (200/1,408). Among subjects in A1 group, the cut point of BMI for predicting EH/EC was 32 kg/m2. Sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), and accuracy were 48.9, 85.7, 28.6, 93.5, and 81.9 percent, respectively. Conclusions: BMI ≥ 32kg/m2 was significantly associated with EH/EC among women age less than 45 years old with abnormal uterine bleeding.